Lower Paleolithic Winds of Change: Prepared Core Technologies and the Onset of the Levallois Method in the Levantine Late Acheulian - Rosenberg-Yefet, T.; Shemer, M.; Barkai, R. (Frontiers in Earth Science, 2022)
The life cycle of a successful technological innovation usually follows a well-known path: a slow inception, gradual assimilation of the technology, an increase in its frequency up to a certain peak, and then a decline. These different phases are characterized not only by varying frequency of use but also by degree of standardization and distinguishability. The Levallois method, a sophisticated Middle Paleolithic technology aimed at producing desired stone items of predetermined morphology, is one such innovation. It has been repeatedly suggested that the Levallois method originated within earlier Lower Paleolithic Acheulian industries, and this work contributes to this discussion. We analyze the reduction trajectory of prepared cores and predetermined blanks from the late Acheulian sites of Jaljulia and Revadim, adding important new evidence for the Lower Paleolithic origins of the Levallois method and its adoption and assimilation in the human stone-tool repertoire of this period in the Levant. Revadim and Jaljulia also provide a rare opportunity to study patterns in the early assimilation of technological innovations. These sites yielded rich lithic assemblages typical of the late Acheulian in the Levant. The assemblages include handaxes but are mostly dominated by flake production technologies and flake-tools. The early appearance of prepared cores at both sites signals, in our view, the inception of concepts related to the Levallois method, termed here proto-Levallois, in the late Acheulian Levant. Through a detailed analysis of prepared cores and their products, we are able to characterize the early stages of assimilation of this method, using it as a case study in a broader discussion of the adoption and assimilation of technological innovations during Lower Paleolithic times.